Expression Of Monoclonal Antibody IBMR3 Antigen In Breast Cancer Tissue - Gazem, Ekhlas Qaid (2016)
The detection of several types of cancer is possible by using monoclonal antibody (MAb). Studies have shown that different types of cancer have related specific abnormal proteins, which are identified by MAb. IBMR3 is a MAb which was raised against synthetic peptides that are associated with the selected amino acid sequence of human interleukin-4 receptors. This research is to detect the expression of IBMR3 antigen in carcinoma including Human laryngeal epithelial carcinoma (HEp-2), Human colon adenocarcinoma (HT-29) and breast cancer tissues. The expression of IBMR3 antigen was detected on HEp-2 and HT-29 using indirect immunofluorescent staining, flow cytometry staining.